Kinetics, thermodynamics, and isotherms studies of Cd(II) adsorption onto grape stalk - Erdem, Mehmet; Duran, Halime; Sahin, Mehmet; Ozdemir, Isilay (Desalination Publ, 2015)
In this study, the ability of grape stalk residue of wine production to remove Cd(II) from aqueous solution by adsorption has been investigated through batch experiments. The grape stalk was characterized in detail by Fourier transform infrared spectrophotometer, scanning electron microscopy, BET, particle size, and elemental analysis. The Cd(II) adsorption property of the grape stalk was evaluated as a function of pH, adsorbent dosage, particle size, initial Cd(II) concentration, and temperature. The adsorption kinetics was evaluated with the pseudo-first-order, second-order kinetics models, and intraparticle diffusion model. The equilibrium data were analyzed using Langmuir and Freundlich isotherms. The adsorption kinetics followed the second-order rate law. The adsorption of Cd(II) onto the grape stalk is fitted to the Langmuir isotherm, and the maximum adsorption capacity was 21.5 mg-Cd(II)/g. Thermodynamic parameters including the changes of enthalpy (Delta H), free energy (Delta G), and entropy (Delta S) were evaluated. The calculated thermodynamic parameters showed that adsorption of Cd(II) was spontaneous and exothermic under examined conditions.
Keywords: Grape stalk; Adsorption kinetic; Cadmium; Isotherm; Thermodynamic